Mathematical model for a backpack load carriage - Abdul Rahman, Sharifah Alwiah; Rambely, Azmin Sham; Ahmad, Rokiah Rozita (2009)
A mathematical model for the analysis of human motion during walking while carrying a backpack is presented in this paper. The model consists of a human torso carrying a backpack in a sagittal plane. The objective of this paper is to develop a model for a backpack load carriage. A Newton-Euler equation is applied to describe the backpack kinematics. Using the inverse dynamics method, the developed model makes it possible to calculate the forces and moments for variation of parameters